2018
DOI: 10.1063/1.5027901
|View full text |Cite
|
Sign up to set email alerts
|

On the wetting properties of human stratum corneum epidermidis surface exposed to cold atmospheric-pressure pulsed plasma

Abstract: The Stratum corneum is the outermost layer of the skin, acting as a protective barrier of the epidermis, and its surface properties are directly related to the spreading of topically applied drugs and cosmetics. Numerous works have been devoted to the wettability of this layer over the past 70 years, but, despite the extensive application of atmospheric-pressure plasmas to dermatology, stratum corneum wettability with respect to plasma-induced species has never been considered. The present report assesses the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 65 publications
1
16
0
Order By: Relevance
“…Recently, improved wettability of the stratum corneum after cold atmospheric plasma treatment has been proposed as an additional effect to facilitate drug delivery through the skin [24,25]. While we have not quantitatively studied the water contact angle in our experiments, in accordance with these studies we have qualitatively observed a substantially improved spreading of water droplets after plasma treatments of skin as well.…”
Section: Resultssupporting
confidence: 77%
“…Recently, improved wettability of the stratum corneum after cold atmospheric plasma treatment has been proposed as an additional effect to facilitate drug delivery through the skin [24,25]. While we have not quantitatively studied the water contact angle in our experiments, in accordance with these studies we have qualitatively observed a substantially improved spreading of water droplets after plasma treatments of skin as well.…”
Section: Resultssupporting
confidence: 77%
“…The specifications of the plasma-jet reactor employed here for the bacterium treatment and the involved physics for the same [29][30][31] or similar [4,5,12,32,72,73] coaxial DBD-based systems have been discussed in these previous reports of our group. The present operational window (see below) is selected as an effective one, based on those previous studies.…”
Section: Plasma Setupmentioning
confidence: 99%
“…Figure 2 presents a typical pair of the driving voltage and the generated DBD current waveforms, as they are recorded by means of a wideband high voltage divider (Tektronix P6015; DC-75 MHz, Beaverton, OR, USA) and wideband current monitor (Pearson Electronics 6585; 40 Hz-200 MHz, Palo Alto, CA, USA), respectively, on a digital oscilloscope (LeCroy WaveRunner 44Xi-A; 400 MHz; 5 GSamples s −1, Chestnut Ridge, NY, USA). Emissive species and gas temperature are identified by UV-visible, high resolution OES, as described in references [4,[29][30][31][32]. In particular, the gas temperature is evaluated by comparing experimentally-determined rotational distributions of probe molecules with the corresponding theoretical ones calculated with a software developed previously [74].…”
Section: Plasma Setupmentioning
confidence: 99%
See 1 more Smart Citation
“…Cold Atmospheric Pressure Plasma jets (CAPP jets) are a hot research topic due their potentiality in many biomedical applications 1 . Indicatively, we refer sterilization 2 , treatment of tissues 3 and liposomes 4,5 , as well as cells including cancer treatment 6 . The study of CAPP jets is based on experiments that aim to characterize the plasma by providing information on the ionic species, the properties of the plasma plume, its temperature, etc.…”
mentioning
confidence: 99%